2005
DOI: 10.1149/1.1872673
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Li Battery Electrolyte Degradation Products Through Direct Synthesis and Characterization of Alkyl Carbonate Salts

Abstract: Aiming toward the identification of carbonate-based electrolyte degradation species formed during high-temperature cycling of Li/M-O cells, we have embarked in the synthesis and characterization of lithium-based alkyl carbonates. Through the reaction of commercial or synthesized lithium alkoxides with carbon dioxide, we succeeded in preparing lithium methyl, ethyl, propyl mono carbonates, and therefore we have extended our work to the synthesis of lithium ethandiol-bis carbonate. Their analytical characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 17 publications
4
116
0
Order By: Relevance
“…Electrolyte salts dissolved in either THF or Et 2 6 could not be measured reliably by NMR spectroscopy. However, in all cases low concentrations of residual salt are observed after the reduction reactions and some of the reduction products may precipitate prior to complete reduction, so the number of electrons required for reduction of the different salts should be viewed as approximate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrolyte salts dissolved in either THF or Et 2 6 could not be measured reliably by NMR spectroscopy. However, in all cases low concentrations of residual salt are observed after the reduction reactions and some of the reduction products may precipitate prior to complete reduction, so the number of electrons required for reduction of the different salts should be viewed as approximate.…”
Section: Resultsmentioning
confidence: 99%
“…The SEI has been proposed to contain lithium alkyl carbonates, lithium carbonate, lithium oxalate, lithium alkoxides, and lithium oxide from the carbonate solvents and LiF, lithium fluorophosphates, lithium fluoroborates, and lithium oxalate from the reduction of electrolyte salts, depending upon the salt utilitzed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Electrolyte additives have also been used to tailor the properties of the SEI through preferential reduction on anode. 1 Despite significant effort over the last two decades, the formation mechanism of the SEI is not well understood.…”
mentioning
confidence: 99%
“…9 For simplicity, Reaction 2.3 in Scheme 1 only depicts the CO 2 generating reaction via the attack at the alkylene carbon, which eventually leads to the formation of poly-EG − . Gireaud et al 13,14 observed the formation of poly-EG oligomers already at 55…”
Section: Mechanism Of H 2 O-and Ohmentioning
confidence: 99%
“…13 Actually, significant evolution of gaseous products such as CO 2 , CO, O 2 , H 2 , CH 4 , C 2 H 4 , C 2 H 6 , C 3 H 6 and C 3 H 8 from the decomposition of carbonate solvents and lithium during battery operation has been detected by various characterization techniques. [14][15][16][17][18][19][20][21] In addition, utilizing isotope analysis, Onuk et al have unambiguously identified the origin of gases evolving in LIBs. 22 Furthermore, by adopting in situ transmission electron microscopy (TEM) 23 and neutron radiography (NR), 9,11 the generation of gaseous bubbles channels formed by the gas have recently been visualized.…”
Section: Introductionmentioning
confidence: 99%